Exploring the Role of Stem Cell Therapy in Improving Cognitive and Physical Outcomes for Down Syndrome Patients - Pada Vinski, Deby Susanti Pada Vinski; Nugroho, Andi Kurniawan; Vinski, Natasha Cinta; Dollar, Dollar; Gunawan, Dahlan (Journal of World Science, 2025)
This review explores the benefits of Mesenchymal Stem Cell (MSC) therapy concerning Down syndrome (DS), cognitive and behavioral disorders, and other related physiological complications. Two pediatric patients with DS participated in this study, receiving MSC therapy over six months through a qualitative case study approach. Patient A was a 5-year-old male experiencing moderate developmental delays and recurrent infections. Patient B was a 6-year-old female facing mild intellectual disabilities and difficulties in social interaction. The initial and follow-up assessments conducted at baseline, three months, and six months after treatment revealed that patients A and B significantly improved in linguistic abilities, attention, social interactions, and motor coordination. Moreover, enhancing inflammatory indices, such as CRP and IL-6, indicated effective regulation of the immune response and reduced inflammation. Both patients adhered to the therapy without any reported side effects. Thus, the findings highlight the potential neuroprotective and immunomodulatory effects of MSC therapy, suggesting it may serve as a viable adjunct treatment for DS. However, due to the limited number of participants and the relatively short observation period, some limitations, such as the small group size and brief study duration, should be acknowledged, necessitating further larger-scale trials to validate these results and establish protocols. This study adds to the existing literature on MSCs in neurodevelopmental disorders and aims to provide a foundation for exploring new treatment options for DS.